Ocular Wnt/β-Catenin Pathway Inhibitor XAV939-Loaded Liposomes for Treating Alkali-Burned Corneal Wound and Neovascularization - Zhong, Yueyang; Wang, Kai; Zhang, Yin; Yin, Qichuan; Li, Su; Wang, Jiaming; Zhang, Xiaobo; Han, Haijie; Yao, Ke (Frontiers in Bioengineering and Biotechnology, 2021)
Corneal wound involves a series of complex and coordinated physiological processes, leading to persistent epithelial defects and opacification. An obstacle in the treatment of ocular diseases is poor drug delivery and maintenance. In this study, we constructed a Wnt/β-catenin pathway inhibitor, XAV939-loaded liposome (XAV939 NPs), and revealed its anti-inflammatory and anti-angiogenic effects. The XAV939 NPs possessed excellent biocompatibility in corneal epithelial cells and mouse corneas. In vitro corneal wound healing assays demonstrated their anti-angiogenic effect, and LPS-induced expressions of pro-inflammatory genes of IL-1β, IL-6, and IL-17α were significantly suppressed by XAV939 NPs. In addition, the XAV939 NPs significantly ameliorated alkali-burned corneas with slight corneal opacity, reduced neovascularization, and faster recovery, which were attributed to the decreased gene expressions of angiogenic and inflammatory cytokines. The findings supported the potential of XAV939 NPs in ameliorating corneal wound and suppressing neovascularization, providing evidence for their clinical application in ocular vascular diseases.